New user? Sign up

Existing user? Log in

Find the value of \(x\) while \[\sqrt{x+\sqrt{x^{2}+\sqrt{x^{3}+\sqrt{x^{4}+...}}}}=\sqrt{2x+1}\]

Note by Jason Snow 2 years, 5 months ago

Easy Math Editor

*italics*

_italics_

**bold**

__bold__

- bulleted- list

1. numbered2. list

paragraph 1paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)

> This is a quote

This is a quote

# I indented these lines # 4 spaces, and now they show # up as a code block. print "hello world"

2 \times 3

2^{34}

a_{i-1}

\frac{2}{3}

\sqrt{2}

\sum_{i=1}^3

\sin \theta

\boxed{123}

Sort by:

Can you write some terms of the series in LHS ?

Log in to reply

Do you know the answer

Desmos says that \(x=4\) but I'm not sure if it's correct

\((n+1)=\sqrt { n^{ 2 }+2n+1 } =\sqrt { 1+\sqrt { n^{ 4 }+4n^{ 3 }+4n^{ 2 } } } =\sqrt { 1+\sqrt { 4{ n }^{ 3 }+\sqrt { n^{6}+8n^6+16n^4}}}\)

continuing the procedure we get

\(\sqrt { 1+\sqrt { 4n^{ 3 }+\sqrt { 16n^{ 4 }+\sqrt { 64{ n }^{ 12 }... } } } } \)

for n=1 we have

\(\sqrt { 1+\sqrt { 4+\sqrt { 16+\sqrt { 64... } } } } \)

squaring then subtracting one from each side we have above equation when \(x=4\)

we have the expression =3 when x=4

the other equation is also 3 when x=4

hence proved

@Hummus A – Thanks !! :D

desmos is right

i'll show you why,it will take a bit of time to type it in LaTeX

We have tried some methods that didn't seem to work, so looking forward to your solution :D

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestCan you write some terms of the series in LHS ?

Log in to reply

Do you know the answer

Log in to reply

Desmos says that \(x=4\) but I'm not sure if it's correct

Log in to reply

\((n+1)=\sqrt { n^{ 2 }+2n+1 } =\sqrt { 1+\sqrt { n^{ 4 }+4n^{ 3 }+4n^{ 2 } } } =\sqrt { 1+\sqrt { 4{ n }^{ 3 }+\sqrt { n^{6}+8n^6+16n^4}}}\)

continuing the procedure we get

\(\sqrt { 1+\sqrt { 4n^{ 3 }+\sqrt { 16n^{ 4 }+\sqrt { 64{ n }^{ 12 }... } } } } \)

for n=1 we have

\(\sqrt { 1+\sqrt { 4+\sqrt { 16+\sqrt { 64... } } } } \)

squaring then subtracting one from each side we have above equation when \(x=4\)

we have the expression =3 when x=4

the other equation is also 3 when x=4

hence proved

Log in to reply

Log in to reply

desmos is right

i'll show you why,it will take a bit of time to type it in LaTeX

Log in to reply

We have tried some methods that didn't seem to work, so looking forward to your solution :D

Log in to reply